Identifying the Potential Determinants of Tobacco Counseling Implementation among Oral Health Professionals of India: A Cross-Sectional Survey - Agrawal, Neha (2023)
Objective: To identify the potential determinants of tobacco counseling implementation among oral health professionals in India. Material and Methods: A cross-sectional survey was carried out among the 298 dentists of Aligarh and Gwalior. The questionnaire used in the study had sections on dentists' sociodemographic data and a 35-item questionnaire to assess the potential determinants of tobacco cessation counseling. Descriptive statistics were carried out, and a Chi-square test was utilized to determine the association. P-value <0.05 was considered statistically significant. Results: Domains "knowledge", "Professional Responsibility and Identity", and "Remembrance, awareness, and judgment" showed a statistically significant correlation with most tobacco cessation counseling behaviors. In addition, undergraduate education received in Tobacco Cessation counseling, and Continuing education received in Tobacco Cessation counseling had significantly impacted the practice of tobacco cessation counseling (p=0.02 and 0.04, respectively). Conclusion: This study suggests that "Knowledge", "Professional Responsibility and Identity" and "Remembrance, awareness, and judgment" are the potential determinants that could be used to design effective strategies to enhance tobacco counseling among dentists in India.